Protein kinases: Role of their dysregulation in carcinogenesis, identification and inhibition - Sarkar, Niloy; Singh, Amit; Kumar, Pankaj; Kaushik, Mahima (Drug Research, 2023)
Protein kinases belong to the phosphor-transferases superfamily of enzymes, which “activate” enzymes via phosphorylation. The kinome of an organism is the total set of genes in the genome, which encode for all the protein kinases. Certain mutations in the kinome have been linked to dysregulation of protein kinases, which in turn can lead to several diseases and disorders including cancer. In this review, we have briefly discussed the role of protein kinases in various biochemical processes by categorizing cancer associated phenotypes and giving their protein kinase examples. Various techniques have also been discussed, which are being used to analyze the structure of protein kinases, and associate their roles in the oncogenesis. We have also discussed protein kinase inhibitors and United States Federal Drug Administration (USFDA) approved drugs, which target protein kinases and can serve as a counter to protein kinase dysregulation and mitigate the effects of oncogenesis. Overall, this review briefs about the importance of protein kinases, their roles in oncogenesis on dysregulation and how their inhibition via various drugs can be used to mitigate their effects.
Keywords: Kinome; Protein kinases; Kinase oncogenic mutations; Kinase identification; Kinase inhibitors; Kinase targets in oncology; gene editing; kinome knockout screen